Comparative Characterization of Phenolic Profile and Antioxidant Activity in Homemade and Commercial Jujube Vinegar - Ana-Maria Stoenescu; Florin Stănică (Beverages)
The growing interest in functional foods has led to a heightened focus on the bioactive properties of different types of vinegar, including jujube vinegar, which has traditionally been valued for its health benefits. This study provides a comparative analysis of the chemical composition and bioactive properties of homemade and commercial jujube vinegar, particularly emphasizing their phenolic profiles and antioxidant activities. Both vinegar samples were analyzed for their physico-chemical properties, phenolic compounds content, and organic acids using high-performance liquid chromatography coupled with mass spectrometry. The results indicated that homemade jujube vinegar contained significantly higher levels of key bioactive compounds, including protocatechuic aldehyde > syringaldehyde > vanillic acid > caffeic acid > gallic acid > protocatechuic acid > chlorogenic acid > p-coumaric and quercetin, compared to the commercial vinegar. Such compounds are widely acknowledged for their antioxidant capacity, anti-inflammatory effects, and overall contributions to human health. The findings suggest that traditional production methods, raw material selection, and fermentation conditions enhance the nutritional potential of jujube vinegar.